Variability of Biochemical Properties During Adaptation of Pinus sylvestris (Pinaceae) Forms to Excessive Moisture Conditions - Sergei N. Tarkhanov; Ekaterina A. Pinaevskaya; Yuliya E. Aganina; Alexander S. Pakhov (Lesnoy Zhurnal (Forestry Journal), 2023)
Conifers are characterized by a certain degree of individual variability in the content of stress metabolites, which can be caused by genotypic variations or divergence in the growth conditions of individual trees. The purpose of the study is to evaluate the variation of biochemical traits of Scots pine, which are different in the color of male strobilus, during adaptation to the conditions of constant excessive moisture in the soil of the northern taiga. The dynamics of metabolic parameters of Pinus sylvestris L. were investigated in shrubsphagnum pine stands on marshy upland soils at the mouth of the Northern Dvina River (northern taiga subzone). From July to November 2018, needle samples from shoots were collected from 10 pine trees of each of the male strobilus types, differentiated by color. The contents of photosynthetic pigments, anthocyanins, ascorbic acid, proline, water-soluble proteins, and pH were measured under laboratory conditions. The synthesis of chlorophyll in the needles in the current year of formation decreased in trees of both forms during the dry summer period. A favorable temperature in the autumn period could promote an extension of photosynthetic pigment accumulation, which might negatively affect tree preparation for overwintering. There were no significant differences between f. erythranthera Sanio and f. sulfuranthera Kozubow in the needle content of chlorophyll and carotenoids, anthocyanins, ascorbic acid, free proline, water-soluble proteins, or pH. The similarities in the adaptation of the trees to the constant excessive soil moisture in northern taiga conditions were revealed. The seasonal factor had a considerable impact on the dynamics of biochemical parameters. Ascorbic acid, proline, and anthocyanin were more actively accumulated in the needles throughout the summer due to the high air temperature, resulting in an increase in antioxidant activity and the development of protective mechanisms aimed at reducing oxidative stress. The increase in water-soluble protein content in ...